The Outcomes of Two Different Suturing Constituents [Chromic Catgut and Polyglycolic Acid (Dexon)] in Episiotomy Repairing - Dr.Sahar Jassim Abid (Scholars Digest Publishing, 2023)
Episiotomy is definite as a perineum surgical incision used during childbirth for increasing vulval outlet diameter. Different kinds of suture constituents are used for episiotomy suturing, commonly used ones are polyglycolic acid (Dexon) and chromic catgut (CC). The purpose of the current work is for comparing the consequences of using the two sutures constituent’s (Dexon) and CC. This study was performed at the Teaching Hospital of Al-Elwiya Maternity and some private hospitals between January 2021 and June 2022. This study is performed through prospective double control study. A total of 150 laboring women with a mean age of 25 years were randomly selected. They were distributed into 2 groups: the 1st one (A) is of 75 women their episiotomies were sutured by Dexon and the other 75 women (group B) their episiotomies were sutured by CC. The women in the hospital observed for the 1st 24 h (haematoma and swelling), 7-10 days postpartum (haematoma, swelling, pain, healing, discharge, wound dehiscence and infection) with one week cover of antibiotics without the use of prophylactic antibiotics, then after puerperium within 6 months, they came back to the hospital in two visits (dyspareunia ,fistula, and stitch removal). P-value ≤ 0.05 was regarded significant statistically.
Keywords: suturing, Dexon, chromic catgut, episiotomy.